Legal Analysis of The Privacy of State-Owned Enterprises - Ahmad Fauzi (Universitas Negeri Gorontalo, 2022)
The world's market economic system influences the management behavior of State-Owned Enterprises which has been lulled by the monopolistic system. The market economic system requires the community as the main actor and the state as the facilitator. Competition occurs in companies as well as in State-Owned Enterprises. To increase efficiency and productivity, must make changes to the management system by making structural adjustments which have been known as restructuring. The government formulates the direction of targets and policies for the management and supervision of State-Owned Enterprises Law Number 19 of 2003 concerning State-Owned Enterprises was made to fulfill the vision of future development; create a management and supervision system based on the principles of efficiency and productivity to improve performance and value in managing and confirming the role of government institutions and the position of government representatives as shareholders or capital owners to emphasize and clarify the relationship as an operator or business actor with a government institution as a regulator; to avoid acts of exploitation outside the corporate mechanism; to lay the foundations or principles of good corporate governance (Good Corporate Governance). The aim is to regulate operations, regulate restructuring, and privatization as a tool and method in State-Owned Enterprises.